Jurisprudential graduation, its concept, types, conditions, and examples of its contemporary application - Alazmi, Nassar Fgaan; Agha, Khlouq Daifallah Moh’d (Journal of Islamic Sciences, 2021)
After God has blessed us and delved into the jurisprudential rulings produced, and the effect of that was to transfer it to the quality of the graduation of rulings, whether on the branches or branches on the branches, I thought that it is necessary to study the fundamental and applied on this, and to clarify contemporary jurisprudential rulings that have been graduated, whether with the origins of the branches or the branches on the branches. The branches where I divided this research into several demands divided into branches to clarify the most important matters related to the issued jurisprudence rulings and the applications contained therein.
Keywords: Islamic jurisprudence; branches of jurisprudence; jurisprudence